PEITC induces apoptosis of Human Brain Glioblastoma GBM8401 Cells through the extrinsic- and intrinsic -signaling pathways. (February 2015) - Chou, Yu-Cheng; Chang, Meng-Ya; Wang, Mei-Jen; Harnod, Tomor; Hung, Chih-Huang; Lee, Hsu-Tung; Shen, Chiung-Chyi; Chung, Jing-Gung
Highlights: We investigate the pro-apoptotic effects of PETIC in human brain GBM 8401 cells. PEITC decreases the cell viability of GBM 8401 cells. PEITC induces significantly sub-G1 phase in GBM 8401 cells. PEITC induces apoptosis through multiple pathways in GBM 8401 cells. We postulate the signaling pathways of PEITC for human brain glioblastoma cells. Abstract: Glioblastoma is the most common and most aggressive primary brain malignancy. The multimodality treatments for this tumor including surgery, radiotherapy, and chemotherapy, are still not completely satisfied. Phenethyl isothiocyanate (PEITC), one member of the isothiocyanate family, has been shown to induce apoptosis in many human cancer cells. In this study, we investigate the pro-apoptotic effects caused by PETIC in human brain glioblastoma multiforme GBM 8401 cells. In our data, PEITC induced the cell morphological changes and decreased the cell viability of GBM8401 cells in a dose- and time-dependent manner. Moreover, the analysis of cell cycle distribution detected by flow cytometry showed that PEITC induced significantly sub-G1 phase (apoptotic population) in GBM 8401 cells. In addition, PEITC promoted the production of reactive oxygen species (ROS) and increase in [Ca2+]I, but decreased the mitochondrial membrane potential (ΔΨm) in treated cells. PEITC also induced caspases activities in GBM 8401 cells. Results from Western blot analysis indicated that PEITC promoted Fas, FasL, FADD, TRAIL, caspase-8, -9, -3, increased the pro-apoptotic protein (Bax, Bid and Bak), and inhibited the anti-apoptotic proteins (Bcl-2 and Bcl-xl) in GBM 8401 cells. Furthermore, PEITC promoted the release of cytochrome c, AIF and Endo G. GADD153, GRP 78, XBP-1 and IRE-1α, Calpain I and II in GBM 8401 cells. PEITC also promoted the expression of associated protein with endoplasmic reticulum (ER) stress. PEITC induces apoptosis through the extrinsic (death receptor) pathway, dysfunction of mitochondria, ROS induced ER stress, intrinsic (mitochondrial) pathway in GBM 8401 cells. The possible molecular mechanisms and signaling pathways of the anti-cancer properties of PEITC for human brain glioblastoma cells were postulated.